ЁШ ГИМНАСТИКАЧИЛАРНИНГ ЖИСМОНИЙ СИФАТЛАРИНИ РИВОЖЛАНТИРИШ - Тўйчиев, З.Ў. (SCIENCE and SOCIETY, 2022)
The set of exercises used in the training process found its practical confirmation in the development of the physical qualities of young gymnasts. General physical training, special physical training, coordination exercises gave technical results to young gymnasts when performing technical training exercises.
Keywords: gym equipment; physical training; technical training; complex exams